Recurrent Episodic Foot-Drop Following Surgery to the Thigh. (2000) - Maiya, Srinivas; Tan, Simon; Grimer, Robert J.
Abstract : Subject. We present the case history of a 47-year-old lady who, 10 months following excision of a soft tissue sarcoma from the left thigh, was struck with recurrent episodes of foot drop. Discussion. The curious phenomenon of recurrent foot drop was found to be secondary to pressure symptoms from a tense seroma of the thigh. She underwent surgical excision of the sac and had immediate and complete relief of symptoms.